Acute LED irradiation does not change the anaerobic capacity and time to exhaustion during a high-intensity running effort: a double-blind, crossover, and placebo-controlled study: Effects of LED irradiation on anaerobic capacity and performance in running - Malta, Elvis De Souza [UNESP]; De Poli, Rodrigo Araujo Bonetti [UNESP]; Brisola, Gabriel Motta Pinheiro [UNESP]; Milioni, Fabio [UNESP]; Miyagi, Willian Eiji [UNESP]; Machado, Fabiana Andrade; Zagatto, Alessandro Moura [UNESP] (Springer Nature, 2016)
The purpose of this study was to investigate the acute effects of photobiomodulation therapy using cluster light-emitting diodes (LEDT; 104 diodes) (wavelength 660 and 850 nm; energy density 1.5 and 4.5 J/cm2; energy 60 J at each point; total energy delivered 600 J) on alternative maximal accumulated oxygen deficit (MAODALT) and time to exhaustion, during a high-intensity running effort. Fifteen moderately active and healthy males (age 25.1 ± 4.4 years) underwent a graded exercise test and two supramaximal exhaustive efforts at 115 % of the intensity associated with maximal oxygen uptake performed after acute LEDT or placebo irradiation in a double-blind, crossover, and placebo-controlled study design. The MAODALT was assumed as the sum of both oxygen equivalents estimated from the glycolytic and phosphagen metabolism pathways during each supramaximal effort. For the statistical analysis, a paired t test was used to determine differences between the treatments. The significance level was assumed as 95 %. In addition, a qualitative analysis was used to determine the magnitude of differences between groups. No significant differences were found for the values of oxygen equivalents from each energetic metabolism (P ≥ 0.28), for MAODALT values between the LEDT and placebo conditions (P ≥ 0.27), or for time to exhaustion (P = 0.80), except for the respiratory exchange ratio (P = 0.01). The magnitude-based inference of effect size reported only a possibly negative effect of photobiomodulation on MAODALT when expressed in units relative to body mass and on the glycolysis pathway (26 %). In summary, LEDT after a high-intensity running effort did not alter the MAODALT, metabolic energy pathways, or high-intensity running performance.
Keywords: Anaerobic capacity; LED therapy; Maximal accumulated oxygen deficit; Photobiomodulation therapy